2020
DOI: 10.1101/2020.07.23.208041
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 receptor Angiotensin I-Converting Enzyme type 2 (ACE2) is expressed in human pancreatic β-cells and in the human pancreas microvasculature

Abstract: SummaryIncreasing evidence demonstrated that the expression of Angiotensin I-Converting Enzyme type 2 (ACE2), is a necessary step for SARS-CoV-2 infection permissiveness. In the light of the recent data highlighting an association between COVID-19 and diabetes, a detailed analysis aimed at evaluating ACE2 expression pattern distribution in human pancreas is still lacking. Here, we took advantage of INNODIA network EUnPOD biobank collection to thoroughly analyse ACE2, both at mRNA and protein level, in multiple… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
99
0
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(117 citation statements)
references
References 84 publications
8
99
0
10
Order By: Relevance
“…T1DM (type 1B subtype) is not a rare condition 24 . Given the fact that ACE2 is expressed on human pancreatic β-cells 4 and that it is the main receptor for SARS-CoV-2 internalization, we propose that, in this patient, direct cytolytic β-cell damage due to SARS-CoV-2 infection resulted in insulin-dependent diabetes with no classical autoimmune pathology evident. This assumption is supported by a recent mechanistic study demonstrating that adult human pancreatic αand β-cells are permissive to SARS-CoV-2 pseudo-entry virus and SARS-CoV-2 virus infection 25 .…”
Section: Autoantibody-negative Insulin-dependent Diabetes Mellitus Afmentioning
confidence: 86%
See 1 more Smart Citation
“…T1DM (type 1B subtype) is not a rare condition 24 . Given the fact that ACE2 is expressed on human pancreatic β-cells 4 and that it is the main receptor for SARS-CoV-2 internalization, we propose that, in this patient, direct cytolytic β-cell damage due to SARS-CoV-2 infection resulted in insulin-dependent diabetes with no classical autoimmune pathology evident. This assumption is supported by a recent mechanistic study demonstrating that adult human pancreatic αand β-cells are permissive to SARS-CoV-2 pseudo-entry virus and SARS-CoV-2 virus infection 25 .…”
Section: Autoantibody-negative Insulin-dependent Diabetes Mellitus Afmentioning
confidence: 86%
“…ACE2 is widely expressed in eukaryotic cell membranes, including those of pancreatic β-cells in mice [18][19][20] and humans 4 . Using a high-fat diet mouse model, it was shown that β-cell de-differentiation is accompanied by reduction in ACE2 (ref.…”
Section: Autoantibody-negative Insulin-dependent Diabetes Mellitus Afmentioning
confidence: 99%
“…This manuscript has been released as a pre-print at https://www. biorxiv.org/content/10.1101/2020.07.23.208041v1 (84).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Therefore, it has been suggested that ACE2 imbalance in the pancreas causes acute beta-cell dysfunction and a resultant hyperglycemic state 14 . Furthermore, the expression of ACE2 has been shown to be increased upon inflammatory stress suggesting an enhancement of the beta-cell sensitivity to SARS-CoV-2 during inflammatory conditions 15 . Acute pancreatitis following COVID-19 has also been reported 16 .…”
mentioning
confidence: 99%
“…The expression of ACE2 in the pancreas is a matter of debate and contradictory results have been reported. For example, three different studies showed a higher expression of ACE2 in the exocrine duct cells than in the islets [17][18][19] , whereas another study showed that ACE2 is preferentially expressed by beta-cells 15 . By single cell sequencing, we have shown that in pancreata from mice, both DPP4 and ACE2 are highly expressed in delta-cells followed by betaand alpha-cells (unpublished data, NATMETAB-A20093633).…”
mentioning
confidence: 99%